Reconstructing Women's Status in Mowea Sarapu: Customary Divorce, Maqasid al-Shari'ah, and Gender Justice in Tolaki Muslim Legal Pluralism, Indonesia - Muh. Akbar Fhad Syahril; Zainuddin Zainuddin; Anatolijs Krivins; Wiwin Wiwin; Nurhaedah Hasan; Hardi Lestari Adi Hafid (Jurnal Theologia, 2025)
This study examines the practice of Mowea Sarapu within the Tolaki Muslim community in Indonesia, focusing on the husband as the primary unit of analysis. In this context, the husband symbolically "hands over" the cheating wife to his lover through the ritual of splitting the sarong and the payment of customary fines, often without formal divorce. The purpose of this study is to examine the conformity of these practices with Islamic norms (marriage, talaq, ishlah, and maqasid al-shari'ah) and to evaluate the normative position of women at the intersection of customs, religion, and state law. Utilizing normative legal research methods with conceptual and comparative approaches, this study draws on a literature review that focuses on the Tolaki/Kalosara tradition, Islamic family law, gender discourse, and Indonesian positive law. The findings suggest that Mowea Sarapu is able to mitigate communal conflict and restore dignity, but it creates a liminal zone for women's legal status, which is vulnerable to livelihood insecurity, hereditary issues, and stigma. The novelty lies in its framing as a reconstructable "ishlah adat." The contribution of research, in the form of socio-theological frameworks (maqasid, legal pluralism, and gender justice), aims to transform it into a model that is women-centered, more equitable, and in line with substantive justice and the rule of law.